Improvement of Catalytic Methane Oxidation by Nitric Acid Treatment on Pt/TiO2 - Jiseok Park; Wo Bin Bae; Sang Woo Byun; Hyeonwoo Shin; Haehyun Min; Young Jin Kim; Sung Bong Kang (Advanced Energy & Sustainability Research)
This study investigates the effect of nitric acid (Pt:NA) treatment on the catalytic performance of Pt/TiO2 catalysts in methane oxidation. By varying the molar ratio of Pt to nitric acid (NA) from 1:0.1 to 1:10 of Pt:NA, a series of Pt/NA‐TiO2 catalysts are synthesized. The structural and catalytic properties are identified using X‐Ray photoelectron spectroscopy, transmission electron microscopy, and diffuse reflectance infrared Fourier transform spectroscopy. The NA treatment during the catalyst synthesis promotes the formation of acidic sites, enhancing the uniform adsorption of the Pt precursor, which in turn improves Pt dispersion and catalytic activity. However, excessive NA treatment above Pt:NA ratio of 1:5 induces the formation of larger Pt particles due to competitive nitrate adsorption, leading to decreased Pt dispersion and diminished catalytic performance. These findings provide a simple method for synthesizing active Pt supported on TiO2 catalysts with NA treatment having well‐dispersed Pt particles, thereby maximizing the catalytic activity of the methane oxidation.